The Diversity of Scarabaeid Beetles (Scarabaeidae: Coleoptera) in The Lowland Rainforest Ecosystem of Sorong Nature Tourism Park, West Papua, Indonesia - Fitradiansyah, La Ode; Atmowidi, Tri; Priawandiputra, Windra; Kahono, Sih (Journal of Tropical Biodiversity and Biotechnology, 2023)
Scarabaeid beetles have an essential role in forest ecosystems, such as nutrient recycling, seed dispersal, forest regeneration, controlling parasite, and reducing carbon emissions. Until now, there has been no publication on scarabaeid beetle diversity in the lowland rainforest ecosystem of Papua, Indonesia. This study aims to measure the diversity of scarabaeid beetles in the lowland rainforest ecosystem of Sorong Nature Tourisme Park (SNTP), West Papua, Indonesia. Determination of study sites used in this study was using the purposive sampling method in three habitat types i.e., rehabilitation zone, conservation zone, and protection zone using baited dung traps (type A, B, and C dung traps), light trap, and active sampling. The fresh cow and human feces baits were used for dung traps that was replaced every 24 hours (68 repetitions for 68 days) in each habitat. Results showed a total of 30 individuals belonging to 13 species of scarabaeid beetles were collected. Onthophagus has the highest species richness (5 species) and the low species richness were Aphodius sp., Anomala sp., and Adoretus sp. (1 species). The protection zone has the highest diversity index (H’=2.09), followed by the conservation zone (H’=2), and rehabilitation zone (H’=0.5). Based on trap type, dung trap collected the most beetle species (9 species), followed by light trap (6 species), and active sampling (2 species). Based on Pearson correlation, soil pH significantly correlated with beetle abundance. This study was the first report of scarabaeid beetles in the West Papua, Indonesia.